RP-HPLC METHOD FOR SIMULTANEOUS ESTIMATION OF FINASTERIDE AND TAMSULOSIN IN TABLET FORMULATIONS - Ashu Mittal; Shikha Parmar; Syed Sarim Imam; Sadaf J. Gilani; Mohd Aqil (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2015)
The object of the present study was to develop a simple, precise simultaneous HPLC method for estimation of Tamsulosin (TAM) and Finasteride (FIN) in bulk and pharmaceutical dosage form. The method involves the use of easily available inexpensive laboratory solvents. The separation was achieved on spherisorb C-18 column with isocratic flow detected at 210nm. The mobile phase consisted of methanol: 0.03mM phosphate buffer pH 3.5 (70:30v/v) with flow rate of 1.0mL/min. A linear response was observed over concentration range of 4-40μg/mL for tamsulosin and 10-80μg/mL for finasteride. Limit of detection and limit of quantitation for tamsulosin were 1.13μg/mL and 3.43μg/mL, and for finasteride were 1.37μg/mL and 4.21μg/mL, respectively. The recovery of tamsulosin and finasteride was found to be in the range of 98.80-100.24% and 99.33-100.33%,respectively. The low %RSD value indicated a good precision and stability of the analytical method. The analysis concluded that the method was selective for simultaneous estimation of tamsulosin and finasteride can be potentially used for the estimation of these drugs in combined dosage form.Key words: HPLC, tamsulosin, finasteride, validation, pharmaceutical dosage form